‘Boys, too, can be objects of desire’: Psychic and Erotic Domination in Eliza Clark’s Boy Parts (2020) - Haro Fernández, Rosa (Complutense Journal of English Studies, 2024)
The present paper aims to analyze the psychic nature of the female protagonist in Eliza Clark’s Boy Parts (2020), as well as her relationships with other characters. For this purpose, I will use psychoanalyst Jessica Benjamin’s theory of intersubjectivity. Benjamin’s intersubjectivity “reorients the conception of the psychic world form a subject’s relations to its object toward a subject meeting another subject”. For my analysis, I will focus on concepts such as recognition, a process of identification with the other, and destruction, a process which allows the individual to go beyond identification with the other and, consequently, to perceive them as a separate self. In Eliza Clark’s Boy Parts, Irina is a photographer who specializes in takes explicit pictures of “interesting”-looking men. The offer of an exhibition at a gallery in London triggers a tailspin of self-destructive behavior partly centered around Irina’s relationship with her best friend, Flo. The analysis of Irina’s psyche and her bonds with Flo and other characters will lead us to conclude that the aforementioned theories provide us with an enriching ground for uncovering the intricacies and what lies at the core of Irina’s psychic nature.